PENGARUH AKSI KORPORASI, EARNING VOLATILITY, DAN NILAI TUKAR TERHADAP STABILITAS HARGA SAHAM DI ERA PANDEMI COVID-19 - Melisa Trisiana; Reni Oktavia; Kiagus Andi (Jurnal Akuntansi dan Keuangan (JAK), 2022)
This study aims to analyze the factors that affect stock price stability as proxied by the volatility of stock prices in the era of pandemic Covid-19. This research examines empirically by using the independent variable of corporate action which is proxied by dividend policy, earning volatility, and exchange rate. Meanwhile, the dependent variable in this study is stock price stability as proxied by stock price volatility. The sample used in this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) for the period January-September 2020 with the purposive sampling method. The population used is 165 companies and a sample of 55 companies. The type of data used is secondary data, and data analysis uses descriptive statistics, classic assumption tests, multiple regression analysis, and hypothesis testing with SPSS 26.0 software. The results of this study indicate that the variable earnings volatility and exchange rates have no effect on stock price stability as proxied by stock price volatility, meanwhile corporate action proxied by dividend policy affects stock price stability as proxied by stock price volatility.